Pengaruh Promosi dan Citra Merek terhadap Keputusan Pembelian Sabun Mandi - Rosiana Dewi; Halimah Zahrah (Indo Publishing, 2026)
This study aims to analyze the effect of promotion and brand image on the decision to purchase Lux brand soap among female Management students of the 2022 class at Muhammadiyah University Bandung. This study uses a quantitative method with a descriptive and verificative approach. The research sample consisted of 52 users of Lux brand soap who were selected using purposive sampling. Data were collected using a questionnaire with a 1-5 Likert scale that had been tested for validity and reliability. Data analysis techniques used multiple linear regression analysis with the help of SPSS version 26. The results showed that promotion had a positive and significant effect on purchasing decisions. Brand image also has a positive and significant effect on purchasing decisions. Simultaneously, promotion and brand image have a significant effect on purchasing decisions with a contribution. Brand image has a stronger influence on increasing the purchase decision of Lux brand soap. The suggestion in this study is to integrate digital promotion strategies with sustainable branding strategies to create strong synergy for stakeholders.